(SnO2) المطعم بالألمنيوم (Al) الدراسة البنيوية و الضوئية و الكهربائية لأكسيد القصدير - مصباحي, نجاح (جامعة الوادي University of Eloued, 2019)
تم الاهتمام خلال هذا العمل بدارسة كل من الخصائص البنيوية، الضوئية و الكهربائية لأغشية أكسيد القصدير النقي (SnO2) و المطعم بالألمنيوم (Al) بنسب (0، 0.2، 0.3، 0.4، 0.5 و 0.8)% ، و ذلك انطلاقا من مادتي كلوريد القصدير (SnCl2) و كلوريد الألمنيوم (AlCl3) يتم ترسيب المحلول على ركائز زجاجية تحت درجة حرارة 480 Cº لمدة 4 دقائق و ذلك من خلال تقنية الرش بالانحلال الحراري. أظهر انعراج الأشعة السينية أن لأغشية أكسيد القصدير المطعم بالألمنيوم بنية متعدد التبلور رباعي الزوايا و تأخذ إتجاهين تفضليين على التوالي(110) و (211) للغير المطعمة و المطعمة أبدت النفاذية الضوئية تزايداً من %83 إلى %86، أما المقاومة السطحية فقد شهدت ارتفاعا من 100.48 إلى 260.29 Ωعند نسبة التطعيم 0.8 %. تتغير قيم الفاصل الطاقي وفقا لنسب التطعيم بالألمنيوم ليأخذ القيم من 3.55 eVإلىeV 3.973.In this work, we studied structural, optical and electrical characterization of undoped tin oxide (SnO2) and aluminum (Al) doped (SnO2) thin films, Which have been deposited from tin chloride (SnCl2) and aluminum chloride (AlCl3) onto glass substrates by spray pyrolysis technique Samples were deposited for 4 minutes at the substrate temperature of 480 °C. the doping concentration of (Al) was varied from (0, 0.2, 0.3, 0.4, 0.5 and 0.8) % in solution. X-ray diffraction (DRX) has Shawn polycrystalline structure according to Tetragonal Rutile (SnO2) and took two favorable directions respectively (110) and (211) as preferential orientation for aluminum (Al) doped (SnO2) thin films. The optical transmittance of (Al:SnO2) films in visible region increases from 83% to 86%. The sheet resistance (Rsh) increased from 100.48 Ω to 260.29 Ω at 0.8% vaccination rate. The optical band gap (Eg) increased from 3.55 eV to 3.973 eV With increasing of the concentration of aluminum (Al) dopants.
مذكرة ماستر تخصص فيزياء
Keywords: أكسيد القصدير(SnO2) ، الرش بالانحلال الحراري، الأغشية الرقيقة، الألمنيوم (Al)، إنعراج الأشعة السينية.; Tin oxide (SnO2), Spray pyrolysis, Thin films, aluminum (Al), X-ray diffraction (XRD).